2009
DOI: 10.1007/s10340-009-0281-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the lectin PHA on the feeding behavior of the grain aphid

Abstract: The electrical penetration graph (EPG) method was used to quantify the effect of the lectin PHA (phytohemagglutinin) on the feeding behavior of the grain aphid Sitobion avenae F (Hemiptera: Aphididae). Addition of PHA to an artificial diet affected aphid probing behavior. In general, increasing concentrations of PHA in sucroseagarose gels significantly reduced the number of aphid probes and extended their duration. Aphids feeding on the gels with lectin (without concentration 50 lg Á cm -3 ) had a prolonged ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Sprawka and Golawska (2010) studied the effects of PHA on the feeding behavior of Sitobion avenae F. by the electrical penetration graph (EPG) method. They could conclude that the addition of PHA to an artificial diet affected the aphid probing behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprawka and Golawska (2010) studied the effects of PHA on the feeding behavior of Sitobion avenae F. by the electrical penetration graph (EPG) method. They could conclude that the addition of PHA to an artificial diet affected the aphid probing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The mannose-binding lectins have shown strong insecticidal activity against chewing and sap-sucking insects, and particularly in controlling aphids (Sauvion et al, 1996;Sadeghi et al, 2009a;Vandenborre et al, 2011). Plant lectins can have detrimental effects on survival, growth, development, and feeding behavior when they are ingested by aphids (Sadeghi et al, 2009a;Sprawka and Golawska, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of ingestion of the disks containing the extracts, the observed nutritional disorders occur. In addition, the effect of deterrence may be related to intoxication (post-ingestion effect), where the insect avoids feeding after ingesting a small amount of food that activates the rejection response (Michiels et al, 2010;Napoleão et al, 2013;Sauvion et al, 2004;Sprawka & Goławska, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PHA has the greatest specificity for complex carbohydrate structures bearing a terminal D-galactose/Nacetyl-D-galactosamine (GalNAc) residue (Goldstein and Portez 1986). The insecticidal activity of PHA on S. avenae may involve effects on enzymes in the gut and on feeding behaviour (Sprawka and Goławska 2010;Sprawka et al 2011). Moreover, immunofluorescent studies by Habibi et al (2000) and Fitches et al (2001a) showed that PHA preferentially binds to the gut epithelial cells, which demonstrate the most severe effects, and that these cells may endocytose the bound PHA.…”
Section: Introductionmentioning
confidence: 99%